Effects of glycine betaine on plant growth and performance of Medicago sativa and Vigna unguiculata under water deficit conditions - Khadouri, Hanan Kamal; Kandhan, Karthishwaran; Salem, Mohammed Abdul (Journal of Phytology, 2020)
Managing water consumption of the crops is one of the strategies which have been adopted locally and worldwide in current trends of sustainable agriculture. In addition to the low level of water resources in UAE because of the rare precipitation, no fresh, free-flowing water, rivers, lakes or streams. The present study was aimed to evaluate the effects of exogenous Glycine Betaine (GB) on Alfalfa (Medicago sativa) and Cowpea (Vigna unguiculata) within different levels of drought stress. A pot experiment was designed on a completely randomized block design (CRBD) with three replicates. Exogenous GB was applied as a foliar spray in three levels (0,100 and 200 ppm) five times with five days intervals. Drought stress starts within the second GB treatment in three levels (24h: 100% well-watered), (48h: 60% water deficit) and (72h: 40% water deficit) depending on the required quantity. Growth characteristics, pigment concentrations, biochemical content and Mineral nutrients levels were measured in response to the treatment variables. Results showed that the GB has a significant increment in Growth parameters, biochemical contents, and Mineral nutrients concentrations. The results of the present investigation suggested that the exogenous application of GB was improved the drought tolerance in Cowpea and has enhanced the Alfalfa performance under drought stress in both concentrations 100 and 200 ppm under drought stress of 60% of irrigations water. In due of comparison of Cowpea and Alfalfa, it’s found from this study that GB has a better effect on the Cowpea under drought stress than Alfalfa.